From Reithian Ethic to Managerial Discourse: Accountability and Audit at the BBC - Born, Georgina (Javnost-The Public, 2003)
This paper outlines the rise during the 1990s of numerous audit and accountability processes within the BBC. It draws on an ethnographic study of the BBC carried out in the later 1990s, which generated an analysis of the internal impact of these changes on the corporation. The paper frames this development within the larger political and governmental contexts to which it was a response. At the same time it notes the absence in this period of significant progress on the part of the BBC in reforming its governance arrangements, a source of continuing criticism of the corporation, and one cause of the voracious growth of auditing. The analysis stresses the visible performance of accountability as an attempted means of strengthening the BBC’s legitimation. It is argued that the processes brought a kind of institutionalised reflexivity to the corporation. At the same time audit and accountability had certain deleterious effects, stoking the growth of tiers of new management, which became an onerous burden on the production arms of the BBC and eroded their creative capacities. The paper therefore questions the utility of the kind and the degree of accountability and audit processes to which the BBC has been subject. It points to an irony: while the implementation of these policies responded to governmental pressures, the BBC’s elaborate performance of accountability and audit has done little to defend it against further encroachment by government in the form of accelerating reviews of its services and delivery.